Cutaneous manifestations among health-care workers caring for COVID patients - Kilaru, Krishna Rajesh; Chekuru, Kavya; Munnangi, Pooja; Chennur, Mallesari; Sukhavasi, Babitha; Kilaru, Manogna Chowdary (International Journal of Research in Dermatology, 2020)
Background: Due to the high transmission ability of the SARS-CoV-2 virus, front-line healthcare workers (HCWs) are at a greater risk of contracting the infection during the management of COVID patients. As a result, prevention measures against COVID-19 disease transmission like personal protective equipment (PPE) and frequent hand washing have become a necessity. While these measures are effective against COVID-19 transmission, they have negative implications as well, one of which is their detrimental effects on the skin. The objective of the study was to understand the prevalence and pattern of cutaneous manifestations among HCWs caring for COVID patients. Methods: A descriptive study on HCWs caring for COVID-19 patients was conducted at a designated COVID hospital from September to October 2020. Data on protective measures taken and cutaneous examination findings were recorded and analyzed. Results: Among 310 HCWs in this study, 137 HCWs (44.19%) had skin rash. The highest incidence of cutaneous manifestations was seen among nurses (48.33%), followed by doctors (42.29%) and support staff (33.33%). Hand eczema (43.80%) was the most common manifestation, followed by acne (22.63%), hair fall (18.98%), sweat dermatitis (11.68%), pressure dermatitis (10.22%), irritant contact dermatitis (7.30%). Seborrhea capitis, pruritus, xerosis, hyperpigmentation, urticaria, tinea corporis, and eczema over legs were the other cutaneous manifestations seen in this study. Conclusions: Nearly half of the HCWs in this study had cutaneous manifestations. Hence, there is a need to educate the HCWs regarding best practices for the prevention of skin damage caused by PPE and frequent hand wash.